(untitled) (Scientific journal of the Fergana State University, 2024)
In this article, on the basis of reforming the training system of future physical education teachers, it is aimed to reveal the pedagogical aspects of the development of acmeological motivation. The research mentioned in the article aims to determine the effectiveness of the application of the acmeological approach and the innovative pedagogical process in the development of acmeological motivation in the future teachers of social education.